Returning the Favor? Feeling Obliged and Reported Participation in Discretionary Safety Activities - Laurent, Julie; Chmiel, Nik; Hansez, Isabelle (Frontiers in Psychology, 2021)
Recent research has shown that employees’ reporting they participate in voluntary safety activities is related to accident and injury outcomes. Encouraging such participation then is beneficial to organizations. A key question therefore is why employees should choose to report that they engage in such activities: what is their motivation given such activities are not compulsory? We use social exchange theory (SET) and organizational support theory (OST) to develop a model linking perceived organizational support to reports of safety participation. SET postulates that benefits given (e.g. by an organization) are reciprocated with potential benefits to the giver as a result. OST emphasises that feeling obliged is a key part of why people reciprocate the support they perceive they get from their organization. Voluntary safety activities have the potential to benefit the organization, so we test for the first time whether there is a link between perceived organizational support and employee reports that they participate in such activities, and whether the relationship is mediated by felt obligation. We test also whether another key SET motivation to reciprocate, anticipated reward, is involved in mediating the relationship. Structural equation modeling using a sample of 536 workers from a Belgian public company involved in the production and distribution of safe drinking water, and in waste water treatment, supported our hypotheses. The model showed that felt obligation mediated the relationship between perceived organizational support and safety participation reports, that anticipatory reward, in the form of perceptions that management were committed to safety, also mediated the relationship between perceived organizational support and safety participation reports. These processes were shown to be separable from employee job engagement and employee perspectives on whether or not voluntary safety activities were part of their job. The findings add to the understanding of why employees choose to report they participate in voluntary safety behaviors by demonstrating for the first time the involvement of felt obligation, but also add to the literature on OST by demonstrating the involvement of perceived management commitment to safety as a mediator between an outcome and perceived organizational support.